OPTIMALISASI KEBIJAKAN KETENAGAKERJAAN UNTUK MENGATASI DAMPAK PHK MASSAL DAN MENINGKATKAN PERLINDUNGAN PEKERJA - Nailatuz Zahro; Irza Annisa Zahra; Anis Monica Sari; Niken Rahmawati; Putri Damayanti; Rizqa Ayu Ambarwati; Amalia Permatasari; Oemar Attallah; Yulianis Satul Faidhah (POLITEKNIK KETENAGAKERJAAN, 2024)
Mass layoffs are a major challenge in the world of labor, which has a negative impact on economic stability and workers' welfare. This article discusses the optimization of employment policies as a solution to address the impact of mass layoffs and improve worker protection. Through an analysis of existing labor policies, this article identifies weaknesses and opportunities for improvement. Optimization of employment policies includes reviewing regulations related to layoffs, strengthening social security programs, and providing training and skills upgrading for affected workers. This policy is expected to minimize the negative impact of layoffs, strengthen the social safety net, and increase the competitiveness of the workforce. The use of normative legal writing methods aims to explore the regulation of workers' rights and legal protection. Based on the study of the optimization of employment policies in overcoming the impact of mass layoffs and increasing worker protection, it is hoped that the optimization of employment policies will become a strategic step in overcoming mass layoffs and increasing protection for workers, thus creating a more stable and productive work environment.